Dependence of the coefficients of residual gases on the type of mixture formation and the shape of a combustion chamber - Корогодский, Владимир Анатольевич; Хандримайлов, Андрей Алексеевич; Стеценко, Оксана Николаевна (Eastern-European Journal of Enterprise Technologies, 2016)
Experimental research and 3D-modeling of gas exchange in a two-stroke engine with spark ignition at the modes of a load characteristic (n = 3000 min-1) have shown how external mixture formation (carburetor power supply system), internal mixture formation (direct fuel injection), and the shape of the combustion chamber affect the coefficient values of residual gases. The calculated mass values of the fresh charge in an engine cylinder differ from the experimental data up to 3% at external mixture formation and up to 9 % at internal mixture formation. Coefficients of the residual gases change in engines: (1) with a symmetric hemispherical combustion chamber and external mixture formation – from 0.17 to 0.24, (2) with a hemispherical combustion chamber shifted to the outlet port and internal mixture formation – from 0.13 to 0.15, and (3) with a symmetric hemispherical combustion chamber and internal mixture formation – from 0.13 to 0.4. It is found that transition from external to internal mixture formation and using a hemispherical combustion chamber would reduce the coefficient values of residual gases up to 41 %.